Effect of Feeding Varying Levels of Lactobacillus Plantarum on Nursery Pig Performance - A. M. Jones; J. C. Woodworth; J. M. DeRouchey; S. S. Dritz; M. D. Tokach; R. D. Goodband (Kansas Agricultural Experiment Station Research Reports, 2016)
A total of 360 pigs (PIC C-29 × 359, initially 13.1 lb BW) were used in a 42-d growth performance trial evaluating the effects of feeding varying levels of Lactobacillus plantarum on nursery pig performance. Pigs were allotted by BW and sex, and randomly assigned to 1 of 4 dietary treatments in a completely randomized design. Experimental diets were fed in three phases (Phase 1, d 0 to 7; Phase 2, d 7 to 21, and Phase 3, d 21 to 42). Treatment diets were formulated to include 0, 0.05, 0.10, or 0.20%Lactobacillus plantarumproduct (LP1; Nutraferma Inc., Sioux City, IA).Lactobacillus plantarumis a facultative heterofermentative plant-associated lactic acid bacterium that is tolerant against bile salts and low pH, improving survivability in the GIT (de Vries et al., 2006; da Silva Sabo et al., 2014). All experimental diets were pelleted. During Phase 1 and 2, there were no differences in growth performance among dietary treatment. During Phase 3, ADG and ADFI were not influenced by treatment; however, increasing LP1 tended to improve F/G (quadratic, P = 0.085) up to the 0.10% level. Overall (d 0 to 42), no differences in growth performance were observed among dietary treatments. In conclusion, increasing dietary levels of LP1 did not impact nursery pig performance.
Keywords: Lactobacillus plantarum; growth performance; nursery pig; probiotic